Enhancing Students' Speaking Skills through Debate Techniques - Evan Afri; Ely Ezir Marpaung; Intan Maulina (ITScience (Information Technology and Science), 2021)
Speaking is considered an essential skill to master. There are some problems with students, lack of communication in class, and lack of vocabulary. The purpose of this study was to improve students' speaking skills through debate techniques. This research method is classroom action research, which is used in two cycles, and each cycle has four steps: planning, action, observing, and reflection. The data presented in this study were obtained from observations, interviews, and students' speaking scores. In this study, the researcher got the result, namely the percentage of speaking. Scores in cycle one 71% passed, and 29% failed; 92% and 8% failed in cycle two. So, the increase in yield in cycle 1 and cycle 2 is 21%. Based on the data above, it can be concluded that learning English, especially speaking through debate techniques, can improve students' speaking skills.